Islam, Ruang Publik dan Kerukunan Antar Umat Beragama (Studi Tradisi Ngebag Kolaboratif di Karangjati Wetan) - Ulinnuha, Roma (Jurnal Sosiologi Agama, 2017)
This article explores how the intersection of religion, religiosity and public segment is more likely manifest in our everyday life. The background of terror and conflicts occurred in the grass roots enacted the social agents to create a more democratic space that is accessible to people, as Jurgen Habermas stated, with diverse setting of religion, ethnicity, social class, education, tribes and other socio-cultural markers. In a sociology-anthropological view, queries include the aspects of religious tolerance in Islam for diverse faiths, the significance of public sphere related to socio-religious entity and the contribution of Ngebag tradition for the model of harmony for inter-religious encounter in Indonesia. The study shows that the creativity of Ngebag tradition served as the arena among the members of sub-urban community in Karangjati Wetan in terms of the actualization of Islamic values. At the same time, the participation of Karangjati people within the tradition accentuated the open access for everyone in a social relation. The tradition contributes to abridge the religious pole and the social one in that people acquire a mode of learning and inspiration such as the hospitality to guests, charity and socialization. Those instances of inspiration can be carried out in the proportional form of everyday social practices in their own situations and contexts. Keywords: Islam, Ngebag, Tradition, Public-Sphere, Conflicts, Harmony